2010
DOI: 10.1002/ajp.20809
|View full text |Cite
|
Sign up to set email alerts
|

Fecal bacterial diversity of human‐habituated wild chimpanzees (Pan troglodytes schweinfurthii) at Mahale Mountains National Park, Western Tanzania

Abstract: Although the intestinal flora of chimpanzees has not been studied, insight into this dynamic environment can be obtained through studies on their feces. We analyzed fecal samples from human-habituated, wild chimpanzees at Mahale Mountains National Park, Tanzania, and compared microbial community profiles to determine if members of the same social group were similar. Between July and December 2007, we collected fresh fecal samples from 12 individuals: four juveniles, four adolescents, and four adults, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
6
20
0
Order By: Relevance
“…This is similar to the bacteria cultured from fecal samples from humans in Africa and Europe16. The high abundance of Firmicutes was reported previously in wild mountain gorillas25, western lowland gorillas26 and also in other primates including old world monkeys27, chimpanzees28 and wild pygmy loris29. Actinobacteria was the second most predominant phylum in our sample; this result is in agreement with the study by Vlckova et al in captive western lowland gorillas26.…”
Section: Resultssupporting
confidence: 92%
“…This is similar to the bacteria cultured from fecal samples from humans in Africa and Europe16. The high abundance of Firmicutes was reported previously in wild mountain gorillas25, western lowland gorillas26 and also in other primates including old world monkeys27, chimpanzees28 and wild pygmy loris29. Actinobacteria was the second most predominant phylum in our sample; this result is in agreement with the study by Vlckova et al in captive western lowland gorillas26.…”
Section: Resultssupporting
confidence: 92%
“…For example, within the pig intestinal bacterial community, one phylotype was identified in the Mycoplasma without any cultured representative category [38]. Recently, the fecal bacterial diversity of the wild chimpanzee (Pan troglodytes schweinfurthii) was examined [39]. One of the phyla identified was Tenericutes, class Mollicutes.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies of rodent and human gut microbiomes are still the most numerous due to the implications of gut microbes in human health and disease, some initial investigations of nonhuman primate gut microbiota composition and function exist. These investigations have generally focused on catarrhines (Frey et al 2006 ;Fujita and Kageyama 2007 ;Uenishi et al 2007 ;Kisidayova et al 2009 ;Nakamura et al 2009 ;Szekely et al 2010 ;Degnan et al 2012 ;Moeller et al 2012 ;McCord et al 2013 ;Moeller et al 2013 ), although other primate taxa, such as the pygmy loris ( Nycticebus pygmaeus ) (Bo et al 2010 ;Xu et al 2013 ) and the black and mantled howler monkeys ( A. pigra, A. palliata ) (Nakamura et al 2011 ;Clayton et al 2012 ;Amato et al 2013 ) also have been sampled. In most of these studies, the main goal is to provide data regarding the composition of the gut microbiota.…”
Section: Application Of Microbiota-centered Models To Other Primate Taxamentioning
confidence: 99%
“…Only one study of 12 wild chimpanzees ( P. troglodytes schweinfurthii ), belonging to the same social group and including parent-offspring pairs, has to some extent provided detailed data at the individual level (Szekely et al 2010 ). However, this study reported that while the most common bacterial phyla (Firmicutes and Bacteroidetes) were shared by all individuals, indices of microbial community similarity were only high among a few samples.…”
Section: Application Of Microbiota-centered Models To Other Primate Taxamentioning
confidence: 99%